2019
DOI: 10.3390/ma12193183
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Interaction between Two Different Types of Nanoparticles and Serum Albumin

Abstract: Two different types of nanoparticles (silicon dioxide and titanium dioxide) were selected within this study in order to analyze the interaction with bovine and human serum albumin. These particles were characterized by transmission and scanning electron microscopy (TEM and SEM), X-ray diffraction (XRD) and energy dispersive X-ray spectroscopy (EDXS). In addition, the hydrodynamic size and the zeta potential were measured for all these nanoparticles. The serum proteins were incubated with the nanoparticles for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…The amide I peak shifted from 1646 to 1657 cm –1 when HSA converted to HSANCs (Figure a). A similar peak shift of amide I (1645–1649 cm –1 ) was observed after the conversion of HSA into its nanoform and was in lieu with our results. Furthermore, the agarose gel electrophoresis displayed the presence of very minute free form of siRNA in the supernatant (lane 2) recovered postsynthesis of si-Bmi1@HSANCs compared with Bmi1 siRNA (lane 1) and pellet recovered (lane 3) diffusing (Figure d).…”
Section: Results and Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The amide I peak shifted from 1646 to 1657 cm –1 when HSA converted to HSANCs (Figure a). A similar peak shift of amide I (1645–1649 cm –1 ) was observed after the conversion of HSA into its nanoform and was in lieu with our results. Furthermore, the agarose gel electrophoresis displayed the presence of very minute free form of siRNA in the supernatant (lane 2) recovered postsynthesis of si-Bmi1@HSANCs compared with Bmi1 siRNA (lane 1) and pellet recovered (lane 3) diffusing (Figure d).…”
Section: Results and Discussionsupporting
confidence: 92%
“…21 The surface and morphological characterizations of nanocarriers were performed using scanning electron microscopy (SEM) (JOEL, JSM-IT300) and transmission electron microscopy (TEM). 23 The functional groups and the secondary structures in HSA and its nanocarriers were analyzed by a Fourier transform infrared (FTIR) spectroscopy 24 and circular dichroism (CD) spectrophotometer (JASCO, J-1500), 25 respectively. The pellets and the supernatant after nanocarrier purification along with bare siRNA were run on 4% agarose gel in 0.5× Tris borate ethylenediaminetetraacetic acid buffer at 80 V for 20 min, and siRNA encapsulation was calculated using following formula.…”
Section: Methodsmentioning
confidence: 99%
“…Even though there is experimental evidence that NP radius only has a modest effect on the affinity of proteins for NPs, , particle size may affect protein conformation and density on NPs, which in turn can affect the reversibility of adsorption. Studies were able to assess protein conformation on NP surfaces over time and suggested that a gradual loss of secondary or tertiary structure was occurring when proteins adsorbed on NPs. ,, Nevertheless, this change of structure does not appear to be systematically correlated with adsorption irreversibility. On one hand, Basu et al observed that structural changes of proteins adsorbed on poly­(lactic- co -glycolic acid) NPs could occur without affecting the reversible nature of the adsorption process .…”
Section: Is Protein Adsorption On Nps a Reversible Or Irreversible Ph...mentioning
confidence: 99%
“…Therefore, our observed HSA dependent PS-particle transfer may be different from physiological HSA processing at the placental barrier. Nevertheless, corona associated albumin can change its conformation, which may directly influence particle transfer in our experiments [57,63]. Whether these results on 80 nm PS-particles are transferable to smaller or larger PS-particles needs to be investigated in future.…”
Section: Discussionmentioning
confidence: 84%